Towards Carbon Neutrality: The Innovation Efficiency of China’s Forestry Green Technology and Its Spatial Spillover Effects - Hangbiao Shang; Chuwei Yang (Land, 2022)
This study evaluates China’s forestry green technology innovation efficiency (FGTIE) using slack-based Data Envelopment Analysis (DEA) based on Chinese provincial panel data from 2011 to 2020. This research endeavours to explore the spatiotemporal dynamics of FGTIE in China and identify its influencing factors. The results demonstrate obvious spatial distribution differences among Chinese FGTIEs, with the southwestern region being relatively stable and the central and southeastern regions being more variable, revealing a general state of clustered development. FGTIE demonstrates a significant spatial correlation. The correlation intensity reveals a ‘W’-shaped, ‘down–up–down’ trend, suggesting that a universal spatial pattern of FGTIE has not yet developed a steady state and that stable spatial aggregation characteristics among provinces are evident. The influencing factors of FGTIE are confirmed to have significant spillover effects. Increases in social security, foreign direct investment and environmental policy stringency will promote efficiency improvements in neighbouring provinces through positive spillover effects, and the economic development level and forestry scale will inhibit efficiency improvements in neighbouring provinces through negative spillover effects.